2018
DOI: 10.1007/978-1-4939-7295-1_9
|View full text |Cite
|
Sign up to set email alerts
|

Designing and Implementing Algorithmic DNA Assembly Pipelines for Multi-Gene Systems

Abstract: Advances in DNA synthesis and assembly technology allow for the high-throughput fabrication of hundreds to thousands of multi-part genetic constructs in a short time. This allows for rapid hypothesis-testing and genetic optimization in multi-gene biological systems. Here, we discuss key considerations to design and implement an algorithmic DNA assembly pipeline that provides the freedom to change nearly any design variable in a multi-gene system. In addition to considerations for pipeline design, we describe p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 23 publications
0
8
0
Order By: Relevance
“…To minimize the confounding effects of medium composition on small molecule titers/yield, we only included used cis-regulatory elements that gave consistent expression of a reporter gene in two growth media, ISM3 and PCNM (Figure 1d and Figure S4). Combining these natural and synthetic genetic elements using one-pot type IIS restriction digestion/ligation reactions, 25 an initial set of seven synthetic gene clusters (SGCs) were produced (Figure 1e). We opted for an iterative DNA assembly pipeline comprising modest (4−5 part) assembly reactions to keep the efficiency high at each step.…”
Section: ■ Resultsmentioning
confidence: 99%
“…To minimize the confounding effects of medium composition on small molecule titers/yield, we only included used cis-regulatory elements that gave consistent expression of a reporter gene in two growth media, ISM3 and PCNM (Figure 1d and Figure S4). Combining these natural and synthetic genetic elements using one-pot type IIS restriction digestion/ligation reactions, 25 an initial set of seven synthetic gene clusters (SGCs) were produced (Figure 1e). We opted for an iterative DNA assembly pipeline comprising modest (4−5 part) assembly reactions to keep the efficiency high at each step.…”
Section: ■ Resultsmentioning
confidence: 99%
“…Our results indicated that Nimble Cloning is not only more convenient than Gibson assembly, but it also results in a higher cloning efficiency (Figure 2A). Previous studies confirmed that Golden Gate cloning, which also involves a one-step digestion/ligation reaction, is more efficient than traditional cloning methods requiring a two-step digestion and ligation reaction (Engler et al, 2009;Hsu and Smanski, 2018). The increased efficiency of onestep cloning may be due to the decrease in the number of steps involving the DNA.…”
Section: Discussion the Advantages Of Nimble Cloning Over Other Methodsmentioning
confidence: 99%
“…pCDS was constructed via with a one-pot Golden Gate assembly as previously described using 5 U Bbs I (New England Biolabs, R0539S) and 5 U T4 Ligase (Promega, # M1804) from two PCR fragments. The origin of replication and selectable Kanamycin marker was amplified using oligonucleotide primers (pCDS_vecF, pCDS_vecR) from plasmid pMJS1AE and lacZα gene product was amplified from plasmid pMJS1AE using oligonucleotide primers (pCDS_lacZF, pCDS_lacZR) that contain lacZ-specific sequences, a Sap I recognition site, 4-bp assembly scar sequence, and an Aar I recognition site.…”
Section: Materials and Methodsmentioning
confidence: 99%
“…CDSs were synthesized by Twist Bioscience (San Francisco, CA) with (5′-atgca­CACCTGCTA­CTA-) and (-TATGGGCAGGTG­atgca-3′) appended to the 5′ and 3′ ends, respectively, to enable modular cloning. CDSs were cloned into the pCDS vector via a one-pot Aar I restriction digestion-ligation reaction (GeneArt Type IIs Assembly Kit, Aar I ThermoFisher Scientific, # A15916) …”
Section: Materials and Methodsmentioning
confidence: 99%